Social Movements and Social Media: A Case Study of the Rejection of Cement Plant Establishment in Rembang Regency - Sitowin, Prasetyo; Rohman, Muhammad Luthfi (Sekolah Pascasarjana Universitas Brawijaya, 2024)
This research aims to understand the role and impact of advocacy through social media in strengthening the Kendeng community movement against establishing a cement factory in Rembang Regency, Indonesia. Utilizing a qualitative method with a descriptive approach, this study employs interviews and documentation as data collection techniques. Data analysis follows an interactive model that includes data condensation, data presentation, and conclusion drawing. The findings reveal that the Kendeng community leverages social media as a principal tool for voicing their aspirations, expanding networks, and mobilizing support. Social media enhances the offline movement by widely disseminating information to the public, while real-action activism remains central. Therefore, this research also aims to explore social media's impact in achieving social movements' goals and whether it serves merely as a trend or has a substantive effect. In the Indonesian context, where conglomerates with vested interests often dominate mainstream media, social media provides an alternative space for marginalized voices. This study contributes to a deeper understanding of the interplay between social media and social movements, highlighting its significance in advocating for social justice, environmental preservation, and democratic participation. Keywords: Kendeng community movement; social media; cement plant rejection; online advocacy; Rembang Regency